(3GddBdi GdeVjI aj CNHGQ CFeI GdRjOjI hGdYJQI GdPcjIs - (3CMeO Hf eMeO Hf UdGM GdTQais; (3TeS GdOjf CMeO Hf YHO Gddg Hf CMeO Hf EHQGgje GdhRjQ,J (B985 (3g` s ((3UdGM Hf CMeO GdegOi Hf eMeO Hf Ydi s)
(3ChdgG (B:s
(3hHYO adeG GfJgi HfG GdebUhO ef PcQ SjQ GdgGOi hef bHdg ef GdCFeI TQYfG ai GdLRA GdKGfi ai PcQ SjQ ef HYOge afbhd ai CNHGQ Hfi GdYHGS s
(3BNQgG (B:s
(3hbhdg (B: (3hgj HdOI ef C(B'(3eGQ PeGQ bGd GdRMja gcPG aSQg GdSjO Je GdLRA GdKGfi hgh BNQ TQM GdHSGeI GdTgjQI HHSGeI GHf GdhRjQ s
(3GNJUGQ dTQM GdRMja Ydi GdbUjOI GdHSGeI ai SjQ CFeI GdRjOjIs
(3hbO CVGa EdgjG GdMhGOK GdeJCNQI HYO (B913(3g Edi SfI (B1053(3g`s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHI s
(3Ydi WQJgG GedcGJ s
(3hYdi ZGTjJgG eWGdYGJ hhba HGSe eMeO Hf eMeO GdgGTei eDQN (B1265(3g` s
Keywords: (3GdJGQjNs